Pengaruh Pemberian Pupuk Trichokompos Kotoran Kambing Terhadap Pertumbuhan Sawi Pahit (Brassica juncea L.) : The Effect of Trichocompost Fertilizer on Goat Manure on the Growth of Bitter Mustard Greens (Brassica juncea L.) - Miftah, Zulfa Rosyidah; Sulistyawati, Sulistyawati; Pratiwi, Sri Hariningsih (Agrotechnology Study Program, Faculty of Agriculture, Wijaya Kusuma Surabaya University, 2023)
Bitter mustard, known as salty mustard or green mustard, is one of the most popular vegetable commodities and has high economic value. Trichocompost is an alternative to increase the growth of mustard greens. This study aims to determine the appropriate dose of goat kohe trichocompost fertilizer to produce high growth and production of mustard greens. Completely randomized design with four treatments, namely M0 : control, M1 : 100 gr.plant-1, M2 : 120 gr.plant-1 and M3 : 140 gr.plant-1 repeated four times. The results of the study concluded that the application of goat trichocompost kohe fertilizer had a significant effect on plant height, number of leaves, leaf area, fresh weight, and dry weight of bitter mustard plants. The best dosage of goat kohe trichocompost fertilizer that can increase the growth and productivity of bitter mustard plants is a dose of 140 gr.plant-1.